Flying not flapping: a strategic framework for e-learning and pedagogical innovation in higher education institutions - Gilly Salmon (Association for Learning Technology, 2005)
E-learning is in a rather extraordinary position. It was born as a ‘tool' and now finds itself in the guise of a somewhat wobbly arrow of change. In practice, changing the way thousands of teachers teach, learners learn, innovation is promoted and sustainable change in traditional institutions is achieved across hundreds of different disciplines is a demanding endeavour that will not be achieved by learning technologies alone. It involves art, craft and science as well as technology. This paper attempts to show how it might be possible to capture and model complex strategic processes that will help move the potential of e-learning in universities to a new stage of development. It offers the example of a four-quadrant model created as a framework for an e-learning strategy.